Analysis of the russian market derivative financial instruments - S. G. Serikov; K. E. Chuprakova (Вестник университета)
The Russian market of derivative financial instruments (hereinafter referred to as derivatives) has been analyzed. Differentiation of the derivatives market have been carried out both by derivatives and by participants. The main leaders have been identified both in the futures and options market as a whole in the derivatives market and in the segments. According to the results of the analysis carried out on the basis of the Moscow Exchange data, the preferential development of index and currency instruments have been revealed, which makes investment companies active in the derivatives market. There is an increase in the volume of commodity derivatives. In general, the Russian derivatives market is characterized by a narrow set of both derivatives and underlying assets, which significantly reduces the range of risks for which hedging is possible in the financial market.